Risk factors of rectocele in women of child-bearing age - Mekan R. Orazov; Lyudmila M. Mikhaleva; Michael V. Krestinin; Mukhammednazar A. Soiunov (LLC "MEDIAFORMAT", 2023)
This article systematically analyses the data available in the current literature regarding the patterns of vaginal wall prolapse with rectocele for-mation. Pelvic floor insufficiency currently occupies one of the leading positions in the structure of gynaecological diseases. However, recent stud-ies do not provide a clear answer on the role of individual risk factors and their combinations in the development of pelvic organ prolapse with rectocele formation.